Comparison of Vitex agnus-castus Extracts with Placebo in Reducing Menopausal Symptoms: A Randomized Double-Blind Study - Naseri, Rozita; Farnia, Vahid; Yazdchi, Katayoun; Alikhani, Mostafa; Basanj, Behrad; Salemi, Safora (Korean journal of family medicine, 2019)
Menopausal symptoms have remarkable negative effects on women's quality of life, justifying the need to assess various therapeutic options. This research aimed to determine the effectiveness of Vitex agnus-castus extracts in alleviating menopausal symptoms in comparison with that of placebo. This study was a randomized controlled double-blind clinical trial with a study group of 52 women referred to a clinic in Kermanshah in 2017. The participants were randomly divided into two groups: Vitex group (26 subjects) and placebo group (26 subjects). Menopausal symptoms were assessed using the Greene Scale before and 8 weeks after the intervention. After the intervention, the mean scores for total menopausal disorder, anxiety, and vasomotor dysfunction were significantly lower in the Vitex group than in the placebo group (P<0.05). The mean scores of the variables of somatic complications, depression, and sexual dysfunction did not show significant differences between the Vitex and placebo groups (P>0.05). Administration of Vitex agnus-castus extracts as a phytoestrogenic medicine can alleviate menopausal symptoms in women.